A framework for a sustainable community-based environmental educational program for Non-Profit Organization (NPO) in the Philippines - Eusebio, Bienvenido C. (Animo Repository, 2011)
Again and again when I talk to volunteers in non-profits, I ask, Why are you willing to give all this time when you are already working in your paid job? And again and again I get the same answer, Because here I know what I am doing. Here I contribute. Here I am a member of a community. (Peter F. Drucker in Managing the Nonprofit Organization: Principles & Practices, 1990. p.xviii) The Non-Profit Organizations (NPOs) primarily staffed by volunteers are very much part of the communities they serve. They increasingly give individuals the ability to perform and to achieve in an endeavor that contributes to the betterment of their community. Precisely because these individuals serve as volunteers, they find more fulfillment and satisfaction out of their contribution. Thus, on the side of the non-profit organization, they have to effectively manage these volunteers. Literature is scant on this subject. Most nonprofit institutions still have to learn how to do so. Using extant literature and a multi-case study method, this research proposes a conceptual framework for a sustainable community based environmental education program for non-profit organization (NPO). It prescribes these four single and interrelated components of an NPO: Leadership, Community Involvement, Sustainability and Environmental Education. This multi-case study looked at three exemplar community-based NPOs. The data and information gathered were analyzed singly for each of the three case studies and cross-case between them Factors, only briefly mentioned in extant literature on NPOs, significant in the success and sustainability of the NPOs in the Philippines were identified: (1) service orientation of an NPO, (2) constituencies commitment to an NPOs vision-mission-goals, (3) culture and its influences on NPO and its programs, and (4) quality of existing relationships among constituencies and its significance in an NPOs resilience in the face of challenges. An emergent framework was generated. To better understand and add knowledge about how to effectively develop and manage NPOs in the Philippines. More research is needed.